Analisis Peningkatan Keselamatan Pengguna Jalan Metode HIRARC (Studi Kasus : Jalan Tol Ruas Pejagan Pemalang) - Moch. Haekal Bahri; Rachmat Mudiyono; Juny Andry Sulistyo (Pondasi, 2025)
Traffic growth on the Pejagan–Pemalang Toll Roadincreases the potential for accidents even though capacity and service levelsare relatively good. This study aims to identify accident-prone locations(LRK) and assess the level of infrastructure risk in order to formulatesafety improvement strategies. The methods used include analysis ofEquivalent Accident Number (EAN) and Cumulative Summary (CUSUM) analysis todetermine accident-prone points, followed by risk evaluation using the HazardIdentification, Risk Assessment, and Risk Control (HIRARC) method. The results of the analysisshow that the priority segments in lane A are KM 297 and 305, while inlane B they are KM 263, 251, and 305. The highest risk levels are at KM 297 A(10.33 – Medium), followed by KM 305 B (9.8 – Medium), KM 305 A (7.38 – Medium), andKM 263 B (6 – Medium). Infrastructure conditions such as damaged guardrails, missing guideposts, open drainage, and unprotected segments are dominant risk factors. Recommendations include the installation of rumble strips, speed reducers, rumble dots, ETLE, pavement repairs, and road improvements tosustainably reduce accident rates.